The permissive non-parental childcare and moral intelligence: Indonesian setting - Falakhul Auliya; Yuli Kurniawati Sugiyo Pranoto; Sunawan Sunawan; Ali Sunarso (Institute of Advanced Engineering and Science, 2021)
Most parents in Indonesia are unable to provide maximum care for their children while working. Childcare includes fostering moral intelligence, which is carried out by grandmothers, household assistants, and daycare assistants. Furthermore, 178 young children (95 males and 83 females) and 178 caregivers (68 grandmothers, 54 household assistants, and 56 daycare assistants) were involved in the study. Simple regression analysis was used to examine parenthood on moral intelligence, and moderator analysis was used to test permissive non-parental childcare and moral intelligence in early childhood. The results showed that authoritative and permissive parenthood has an effect on moral intelligence and that the effects of permissiveness on moral intelligence are only moderately influenced. Permissive non-parental childcare and moral intelligence apply to the group of grandmothers and household assistants. The research provides a detailed description of the role of predictors on moral intelligence in non-parental care.